Beliefs about obesity and their relationship with dietary restraint and body image perception - Magallares, Alejandro; Carbonero-Carreño, Rocio; Ruiz-Prieto, Inmaculada; Jauregui-Lobera, Ignacio (Anales de Psicología / Annals of Psychology, 2016)
Recent studies provide evidence that beliefs about the causes of obesity may actually have an influence on eating habits. In this work we wanted to analyze the relationship that may exists between beliefs about obesity, dietary restraint and body image perception. For that purpose, 258 students of a High School and Occupational Training School in Seville (Spain) were recruited to conduct the study. According to our results, it was found that beliefs about obesity were positively related with dietary restraint and body image perception. Additionally, it was found that people high in beliefs about the controllability of the weight scored more in dietary restraint and body image perception than participants that did not believe that obesity was under personal control. No differences were found in Body Mass Index. Finally, it is suggested, according to the results that we found, that in order to be effective, public health campaigns may need to target people’s beliefs just as much as they target their behaviours.